What determines forward-looking information disclosure in Bangladesh? - Pappu Kumar Dey; Manas Roy; Mohsina Akter (Asian Journal of Accounting Research, 2020)
The study aims to examine the level and extent of forward-looking information (FLI) disclosure and identify the determinants driving the FLI disclosure (FLID) in the context of an emerging and developing economy.The sample includes annual reports of the top 30 listed companies in Bangladesh for the years 2013–2017. The content analysis approach is used to examine the practice of FLID and to determine the extent of FLID based on the index. Multiple linear regression analysis is performed to identify the determinants of FLID.This research finds that board size, auditor's global affiliation, leverage and profitability have a substantial positive impact on FLID. By contrast, firm size and listing age have a significant negative association with FLID. Moreover, contrary to our expectation, female representation in the boardroom has an inverse effect on FLID. This study, however, does not suggest any significant impact of board independence.Small sample size may limit the generalizability of the findings. Besides, the FLID index score may be affected by the subjective judgment while analyzing the content of the annual report.The findings of this paper may assist the regulators and policymakers in incorporating this new reporting paradigm in regulations. Alternatively, the current research can serve as a basis to further understand the importance of FLID for the stakeholders.This empirical study contributes to the current FLI literature in Bangladesh. A handful of studies have been done to examine the nature and level of FLID and find out the determinants of FLID in the developing countries. To the best of the authors' knowledge, no study yet has been explored on FLID and its determinants by classifying them as qualitative and quantitative in Bangladesh.